Effect of porosity on the structure, mechanical properties and cell viability of new bioceramics as potential bone graft substitutes - Demirel, Mehtap; Aksakal, Bunyamin (WROCLAW UNIV TECHNOLOGY, 2018)
Porous and alternative biografts for possible usages in orthopaedic applications were synthesized by the substitution of gelatin (G), cuttlefish backbone (C), meerschaum sepiolite (S) and hydroxyapatite (H). The effects of different proportions of the Gelatin substitutions on the mechanical properties and structure and cell viability properties of the fabricated biografts were investigated. Throughout the structure and mechanical evaluations, it was found that Gelatin substitution in the fabricated biografts increased the total porosity fraction, particularly for C13G75 and S13G75 biografts. Scanning Electron Microscope (SEM), X-ray diffraction (XRD) and Fourier Transform Infrared Spectroscopy (FTIR) were used for characterization of the synthesized biografts. Furthermore, the cell viability tests for the synthesized biografts were carried out by using the osteoblast cell culture. Throughout the analysis, the synthesized C13G75 and S13G75 biografts generated the highest porosity and better correlation between mechanical properties and structural results contributing with highest cell viability rates.
Keywords: bone graft; hydroxyapatite; sol-gel; porosity; mechanical properties; TRABECULAR BONE; SCAFFOLDS; PHOSPHATE; CUTTLEFISH; GELATIN; TISSUE; Biophysics; Engineering